ICTs: interfaces between people and places - Morandi, Corinna; Rolando, Andrea; Di Vita, Stefano (TeMA - Journal of Land Use, Mobility and Environment, 2013)
Although the spread of the smart city paradigm has been exponential, with a consequent decrease of part of its meaning, the smart city concept still suggests a system of innovative theories and practices. In this sense, the research “The smart region between Turin and Milan. Mobile services as drivers of spatial innovation towards Expo 2015” (Politecnico di Milano-Telecom Italia) is proposed as an opportunity for exploring the use of Information and Communication Technologies (ICTs) to promote an integrated system of services at the regional scale, also in perspective of the 2015 Universal Exhibition. Considering the transformation of universities into one of the major players in the current processes of urban and regional development, the research (in progress) has chosen to focus on the physical and immaterial services provided by university campuses. The operational phase of the research was developed in the second half of 2012, with a first focus on the Città Studi area in Milan, where the Sustainable Campus project (promoted by Politecnico and Università degli Studi di Milano) is going on. The outcome of the first implementation phase of the research has been the preliminary set up of two smartphone applications and the following development for the prototype of one of them. These APPs refer to some critical issues within the campus: the sharing of spaces for free study and work and the management of the demand and supply for the students housing. The project has also allowed to test a methodology with the aim of understanding the needs and of identifying the opportunities for the development of mobile services as interfaces between people and places in the campus and its urban context.